W obawie przed islamizmem. Uwagi na marginesie książki Krzysztofa Izaka - Sadowski, Mirosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
In the article the author analyses Krzysztof Izak’s book The Lexicon of Radical Organisations and Islamic Movements. Hepolemicizeswith some of the theses proposed inthe Lexicon, with the descriptions of wahhabism, jihadism, or radicalism in particular. On the other hand, the author also notes that K. Izak managed to present the complexity of islamic radicalism in a very clear way. In conclusion, M. Sadowski highlights the scientific and epistemic merits of the Lexicon, noting that it does not have any equivalents in the Polish scientific literature concerning this subject.
Keywords: islamizm; Izak, Krzysztof; ruchy islamskie; wahhabizm; święta wojna